Gaps in the researches about Science and Adult education teaching: indicative about an universe to explore. - Sirliane da Costa Viana; France Fraiha- Martins; Joyce Melo Mesquita (Amazônia, 2022)
This paper gives attention to analyze the scientific productions about Science and Adult education teaching (EJA) in two digital platforms which has an academic relevance and promote and socialize researches about education. The study has explored published data in the period from 2009 to 2019 in the Coordination for higher Education Staff Development (CAPES) and National Association of post-graduation and researches in education’s platforms (ANPED). Both researches sources are important scientific productions representatives in education in Brazil, specially about initial schooling, including EJA. The productions’ mapping at CAPES and ANPED confirm the necessity and importance about intensifying the development of more researches which discuss more about science teaching at EJA, not only about initial production, they are highlighted in most of the academic researches which were analyzed, but due to its relevance, inclusive, through the critical training in which people are able to identify and analyze the economic development models, politics, social, scientific, technological and environmental which are included.